Strategi Pengembangan Pemasaran Digital Menggunakan Blogger pada UMKM Dimsum By Kalili di Kota Padang - Fachrul Nugraha; Siti Komaryah; Hannisa Syifa Salsabilla; Sularno; Rafidola Mareta Riesa (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This study presents a comprehensive and in-depth analysis of the development strategy for digital marketing using Blogger as a platform for Dimsum By Kalili, a micro, small, and medium-sized enterprise (UMKM) specializing in coffee products in the city of Padang. By examining Dimsum By Kalili current digital marketing efforts and evaluating the potential benefits of incorporating a blogger strategy, this paper aims to propose a robust and effective roadmap for Dimsum By Kalili digital marketing development. The strategy begins with a thorough examination of the target audience, identifying their preferences, demographics, online behavior, and consumption patterns. This step enables Dimsum By Kalili to tailor its content and marketing strategies to effectively engage with its target customers. In addition, the study emphasizes the importance of creating valuable and compelling content that resonates with the audience's interests, needs, and desires. Furthermore, the proposed strategy encompasses search engine optimization (SEO) techniques to ensure better visibility and discoverability of Dimsum By Kalili blog. By optimizing keywords, meta tags, and other on-page elements, Dimsum By Kalili can improve its organic search rankings and attract a larger audience. The study also highlights the significance of integrating social media platforms into the strategy, allowing Dimsum By Kalili to extend its reach and foster stronger customer relationships through interactive and engaging content. In conclusion, this study provides a comprehensive roadmap for Dimsum By Kalili digital marketing development using Blogger. Through a targeted approach to audience analysis, content creation, SEO techniques, and social media integration, Dimsum By Kalili can establish a strong online presence, cultivate customer relationships, and increase its market share in the competitive UMKM industry of Padang city.